Diversity and Abundance of the Commercial Fish at Some Coastal Coral Reef Bays in Marsa Alam, Red Sea, Egypt - Abu El-Regal, Mohamed; Maaty, Mahmoud; Farhat, Aml; Azab, Ahmed (Journal of King Abdulaziz University: Marine Sciences, 2024)
This work aimed to study the structure of the commercial fish communities at six coastal coral reef bays around Marsa Alam city on the southern coast of the Egyptian Red Sea. Fish communities were counted in Marsa Saifen, Marsa Shoni2, Marsa Shoni4, Marsa Fujiri, Marsa Nakari and Marsa Hamata using underwater visual census technique (UVC). A total of 2458 fish belonging to 16 families and 44 species of commercial fish were found. Five families (Scaridae, Serranidae, Mullidae, Lutjanidae and Lethrinidae) contained 27 species (61.4% of the total number of species). Four families (Mullidae, Siganidae, Scaridae and Lutjanidae) were the most abundant and they formed about 91.3% of the total number of recorded individuals. Mullidae was the most abundant constituting about 63.5% of the fish community). The most abundant species was Mulloidichthys flavolineatus, of the family Mullidae with 1390 individuals forming 56.5%, followed by Siganus rivulatus of the family Siganidae (251, 10.2%). The highest abundance of fish was recorded in Marsa Saifen (609 individuals) and the lowest abundance was recorded at Hamata (271 individuals). The highest number of species (23 species) was observed in Marsa Fujiri, whereas the lowest number of species (17 species (was recorded in Hamata. This study concluded that knowledge of the ecology of marine fish communities in the Red Sea is sparse and hence quantitative ecological studies are needed. Action plans and research programs must be developed to reduce early stages bycatch and initiate fisheries management strategies for commercially exploited species.